2000
DOI: 10.1128/iai.68.2.564-569.2000
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Affinity Purification, and Identification of Piglet Small Intestine Mucosa Receptor for Enterotoxigenic Escherichia coli K88ac+ Fimbriae

Abstract: An affinity chromatography technique was utilized to isolate and purify the receptors of Escherichia coli K88ac؉ fimbriae from the mucus of the small intestines of newborn piglets. Purified K88ac؉ fimbriae were covalently immobilized onto a beaded agarose matrix (Sepharose 4B). The immobilized fimbriae were used for the affinity purification of the K88ac؉ receptors. Only two major proteins were tightly and specifically bound to the immobilized fimbriae after the column containing bound receptor was washed exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…These results showed the highest percentage of adhesive strains in the caecum and intestine compared with faeces. Pathogens as Escherichia coli that inhabit the gastrointestinal tract of pigs present surface proteins that recognise in a specific manner receptors in the mucus (Fang et al, 2000). Moreover these results support the previously observed by Namba et al (2007) who reported that intestinal bacteria which colonise the surface of intestinal mucosa, showed a high-adhesive capability to fish intestinal mucus.…”
Section: Resultssupporting
confidence: 82%
“…These results showed the highest percentage of adhesive strains in the caecum and intestine compared with faeces. Pathogens as Escherichia coli that inhabit the gastrointestinal tract of pigs present surface proteins that recognise in a specific manner receptors in the mucus (Fang et al, 2000). Moreover these results support the previously observed by Namba et al (2007) who reported that intestinal bacteria which colonise the surface of intestinal mucosa, showed a high-adhesive capability to fish intestinal mucus.…”
Section: Resultssupporting
confidence: 82%
“…In addition, the receptor to which it binds must be somewhere other than in brush borders, because MAb 36/41 blocks the binding of K88ac to porcine enterocyte brush borders of phenotypes A and B, the only brush borders to which K88ac binds (1). It has been suggested by other investigators that the mucus covering the intestinal epithelium contains glycoproteins to which K88 fimbriae bind and that these glycoproteins may serve as receptors for the adherence of bacteria to that mucus (6,10). The mucus glycoproteins identified were different from the receptors previously identified on porcine enterocyte brush border membranes (10).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested by other investigators that the mucus covering the intestinal epithelium contains glycoproteins to which K88 fimbriae bind and that these glycoproteins may serve as receptors for the adherence of bacteria to that mucus (6,10). The mucus glycoproteins identified were different from the receptors previously identified on porcine enterocyte brush border membranes (10). If the fimbrial tip subunit is adhesive, it may bind to mucus glycoproteins or perhaps to receptors found on the epithelium in another part of the gastrointestinal tract or in an alternative host.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal mucus secretion assay was performed by a previously described method (15), with modifications. Briefly, adult BALB/c mice that were kept without food for 24 h were orally incubated with 1 ml of overnight cultures of V. cholerae N16961, N1RB3, or N1RC2.…”
Section: Methodsmentioning
confidence: 99%